Riboregulation in the Major Gastric Pathogen Helicobacter pylori - Tejada-Arranz, Alejandro; De Reuse, Hilde (Frontiers in Microbiology, 2021)
Helicobacter pylori is a Gram-negative bacterial pathogen that colonizes the stomach of about half of the human population worldwide. Infection by H. pylori is generally acquired during childhood and this bacterium rapidly establishes a persistent colonization. H. pylori causes chronic gastritis that, in some cases, progresses into peptic ulcer disease or adenocarcinoma that is responsible for about 800,000 deaths in the world every year. H. pylori has evolved efficient adaptive strategies to colonize the stomach, a particularly hostile acidic environment. Few transcriptional regulators are encoded by the small H. pylori genome and post-transcriptional regulation has been proposed as a major level of control of gene expression in this pathogen. The transcriptome and transcription start sites (TSSs) of H. pylori strain 26695 have been defined at the genome level. This revealed the existence of a total of 1,907 TSSs among which more than 900 TSSs for non-coding RNAs (ncRNAs) with 60 validated small RNAs (sRNAs) and abundant anti-sense RNAs, few of which have been experimentally validated. An RNA degradosome was shown to play a central role in the control of mRNA and antisense RNA decay in H. pylori. Riboregulation has also been revealed and depends both on antisense RNAs and small RNAs. Known examples will be presented in this review. Antisense RNA regulation was reported for some virulence factors and for several type I toxin antitoxin systems, one of which controls the morphological transition of H. pylori spiral shape to round coccoids. Interestingly, the few documented cases of small RNA-based regulation suggest that their mechanisms do not follow the same rules that were well established in the model organism Escherichia coli. First, the genome of H. pylori encodes none of the two well-described RNA chaperones, Hfq and ProQ that are important for riboregulation in several organisms. Second, some of the reported small RNAs target, through "rheostat"-like mechanisms, repeat-rich stretches in promoter regions of genes encoding important virulence factors. In conclusion, there are still many unanswered questions about the extent and underlying mechanisms of riboregulation in H. pylori but recent publications highlighted original mechanisms making this important pathogen an interesting study model.